2012
DOI: 10.1159/000338168
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Changes on the Intestinal Mucosa in Orthotopic Neobladder

Abstract: Introduction: The intestinal mucosa undergoes significant atrophic changes when it is used to reconstruct the urinary tract. We analyzed the ultrastructural changes of intestinal mucosa in the orthotopic neobladder on the basis of our clinical experience. Patients and Methods: Fifteen male patients with an ileal neobladder underwent endoscopic biopsy at different postoperative intervals. Results: No significant changes were observed 3 months after surgery. After 6 and 12 months, the structure of the microvilli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The ureters are connected to this reservoir, which in turn is reconnected to the urethra to allow patients to urinate normally (Freeman et al 1996;Stein et al 2005;Hautmann et al 2007). The autologous transposition of the small intestine to form a neobladder marks the precise time point when the tissue becomes exposed to a foreign bladder environment in which low intraluminal pH and various urinary solutes trigger pathophysiological changes in the otherwise normal intestinal mucosa (Philipson et al 1987;Aragona et al 1998;Gatti et al 1999;Di Tonno et al 2012). The neobladder, however, maintains the blood supply of the original tissue so that the predominant change of the local tissue environment is in the content of the lumen to which the intestinal cells are exposed.…”
mentioning
confidence: 99%
“…The ureters are connected to this reservoir, which in turn is reconnected to the urethra to allow patients to urinate normally (Freeman et al 1996;Stein et al 2005;Hautmann et al 2007). The autologous transposition of the small intestine to form a neobladder marks the precise time point when the tissue becomes exposed to a foreign bladder environment in which low intraluminal pH and various urinary solutes trigger pathophysiological changes in the otherwise normal intestinal mucosa (Philipson et al 1987;Aragona et al 1998;Gatti et al 1999;Di Tonno et al 2012). The neobladder, however, maintains the blood supply of the original tissue so that the predominant change of the local tissue environment is in the content of the lumen to which the intestinal cells are exposed.…”
mentioning
confidence: 99%
“…Changes to the novel urinary microenvironment have been hypothesised to promote this gradual stabilisation of renal function in ONB recipients. Previous studies have shown that prolonged contact with urine likely induces progressive blunting of microvilli throughout the neobladder intestinal segment [12,13]. Such morphological changes in the neobladder mucosa better approximate the uroepithelium, thus reducing the absorptive surface area for electrolyte exchange, resulting in decreased long‐term risk of metabolic acidosis due to ileal absorption of urinary ammonium.…”
Section: Discussionmentioning
confidence: 99%
“…However, after 3-6 months after surgery, atrophic changes in the intestinal mucosa lining the neobladder occur, and consequently, the neobladder is less susceptible to bacterial colonization and infection. 20,21 Finally, prolonged urinary catheterization is related to UTI. For these mechanisms, it can be suggested that UTI rate in patients with ONB decreases overtime especially after 3 months postoperatively.…”
Section: Discussionmentioning
confidence: 99%